STRATEGIC DECISIONS OF STUDENTS: DETERMINATION OF OWN LIFE POSITION - Помиткіна, Л. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2014)
The article reveals psychological features of strategic life decision-making considering determination of own life position, analyzes different views of scientists, presents results of empirical research of features of strategic life decision- making by students considering determination of own life position. Making strategic life decisions is a difficult personally-determined cyclical process, based on psychic turnover, updates value-motivational, emotional and sensual, intellectual and determined psychological mechanisms and leads to life self-determination, reduction of uncertainty of initial choice situation. In the basis of all decisions there is a life position of an individual, as the process of its formation occurs comes from childhood. The results of empirical researches showed that strategic life decision-making by students to determine own position in life is a conscious act of self-knowledge and self-constitution based on value orientation of a person in environment, including evaluating attitude to themselves and others as a result of learning social norms and under the influence of cultural environment